CRITICAL THINKING FOUNDATIONS AS A TOOL OF MANIPULATIVE TECHNOLOGIES RECOGNITION - Pelepeychenko, Ludmyla; Revutska, Svitlana; Babkov, Yurii (Honor and Law, 2022)
The aim of the article was to substantiate the cognitive foundations of critical thinking that provide recognition of manipulative technologies. The substantiation of cognitive foundations of critical thinking, aimed at recognition of manipulative technologies, is carried out on the basis of available scientific achievements in the field of general matters of critical thinking, which are projected on the sphere of manipulative influence. The paper gives the definition of cognitive foundations that include knowledge, skills and abilities and personal attributes required for effective intellectual analysis. The following types of cognitive foundations of critical thinking are modeled and substantiated in the article: 1) knowledge; 2) skills and abilities; 3) personality traits that are actualized in the process of intellectual activity (intellectual traits). The first type of cognitive foundations are both awareness of the social context and awareness of the generally accepted value priorities of civilized society. Cognitive foundations of the second type include 10 skills, namely: finding of logical contradictions and errors; lie recognition; distinguishing between real and fictional facts; distinguishing between correct and erroneous statements; mastery of general scientific methods of analysis; establishment of the source base; argumentation; refutation of misconceptions; recognition of indicators of manipulative influence; modeling of solution options. Cognitive supports of the third type are as follows: observation, ability to perform analytical operations. The article demonstrates how skills and abilities are used in detection of textual and non-textual indicators of manipulation. Textual indicators include those that are contained in the very text of the message (logical contradictions, ambiguity of the statement, violation of the clarity of information and its completeness). Non-textual indicators are those for the recognition of which it is necessary to correlate the narrative with real events, with the logic of the relationship of events and facts as well as with ideological attitudes of the authors of the messages.